A high‐speed, salt‐free, and dyebath‐recyclable circular coloration technology inspired by mussel bionic. Issue 47 (3rd October 2022) - Li, Fenghua; Liu, Man; Yan, Dexiang; Yin, Zonggong; Xiao, Jiahong; Sun, Bin; Shen, Yuhong; Gao, Tingting; Liu, Qinze; Zhou, Guowei
Abstract: With the current situation of high‐energy consumption and high pollution in the textile industry, developing an eco‐friendly and universal dyeing technology is urgently required. Towards this goal, in this study, the dyeing technology with room temperature, salt‐free, zero release, and rapid cycle dyeing for 20 min was realized using a polymer of catechol and polyethyleneimine as a dye. The dyed fabrics exhibited washing, rubbing, and perspiration fastness characteristics for practical needs, mainly attributing to the hydrogen bonding and π–π interaction between the dye molecules and the fabrics. Benefiting from the unique dyeing technology, the dyed fabrics show excellent leveling properties and adjustable chromaticity. Importantly, the mussel‐inspired coating strategies are universally applicable, so the dyeing technology can be applied to various fabrics. Consequently, the environmentally friendly dyeing process based on low‐cost catecholamine polymers as a dye will have a broad application prospect in the printing and dyeing industry. Moreover, the antibacterial tests showed that dyed cotton cloth, mulberry silk, and polyester fabrics all have favorable antibacterial properties, especially dyed mulberry silk fabrics have a greater than 90% bacterial reduction rate for both Escherichia coli and Staphylococcus aureus . Abstract :